Collective efficiency of the soy cluster (Glycine max L.): Tamaulipas Case, Mexico (Agro Productividad, 2020)
Objective: To analyze the collective efficiency (CE) of the soy cluster (Glycine max L.) in the southern region of Tamaulipas, Mexico.Design/methodology/approach: The Localization Coefficients and Gini indexes were calculated for the soy sector in thestate, based on information obtained from SIAP (2018). The Collective Efficiency Index was obtained from the soy cluster, through the application of a questionnaire to producers in the region for the measurement of external economies and joint actions in the agglomeration.Results: The indicators allowed identifying a high concentration of the soy sector in the southern region of Tamaulipas, in addition to the participation of a high proportion of the municipalities in production, production value, surface sown, and surface harvested. It was identified that the producers in the soy conglomerate have achieved a middle level of CE, with a higher presence of Joint Actions (JAs) than External Economies (EEs).Study limitations/Implications: It is a transversal study, because the CE was only studied in the soy cluster during a specific period.Findings/Conclusions: Although the soy cluster in the region evaluated offers its members various benefits, the maximum development of their CE has still not been attained, which is why there is still a need to continue strengthening the sector by the state government, through programs that promote individual and collective development of soy producers and organizations related with the sector located in the region.